Hybrid Approach to Curriculum Development for the Indonesian Context: A Theoretical Study in the Independent Curriculum Era - Gaffar Aiman Nafis; Zainal (Cipta Pustaka Nusantara, 2025)
The implementation of Indonesia’s Merdeka Curriculum provides broad flexibility for schools to design learning based on students’ needs and contextual characteristics; however, its adoption continues to face challenges related to unequal access, varying levels of teacher readiness, and disparities in school resources. This study aims to formulate a hybrid curriculum model that offers a more adaptive and equitable approach to curriculum development suited to Indonesia’s diverse educational landscape. Employing a library research method with a descriptive–analytical approach, the study systematically reviewed relevant literature published within the last five years, focusing on curriculum development models, Merdeka Curriculum implementation, teacher readiness, and educational access gaps. Data were analyzed through thematic categorization, comparative evaluation, and conceptual synthesis. The findings indicate that no single curriculum model sufficiently addresses Indonesia’s complex educational context, thereby necessitating a hybrid approach that integrates national standards with localized adaptability. The proposed hybrid curriculum consists of three interconnected components core, adaptive, and support elements which collectively ensure both flexibility and consistency in instructional quality. The study’s implications highlight the importance of systemic support, including teacher training, provision of minimum learning resources, and targeted affirmative policies, to enable widespread and sustainable implementation. This research contributes a conceptual framework for curriculum development and provides a foundation for future empirical studies exploring hybrid curriculum practices in diverse school settings